Luke the Composer : Exploring the Evangelist's Use of Matthew - Mosbo, Thomas J. (Book collections on Project MUSE., 2017)
Thomas J. Mosbo argues that no theory of Synoptic relations is adequate unless it can satisfactorily explain the extensive middle third of Luke's Gospel, the so-called Travel Narrative (9:51-19:27), where Luke departs from the order shown in either Matthew or Mark and assembles stories and sayings that develop themes concerning discipleship that are important to Luke. Mosbo shows how Luke has in fact reordered materials taken from Matthew and Mark in a very particular manner, then Mosbo offers his own hypothesis of the relationship between Matthew and Mark.